Deimmunizing substitutions in Pseudomonas exotoxin domain III perturb antigen processing without eliminating T-cell epitopes - Moss, Daniel L.; Park, Hee-Won; Mettu, Ramgopal R.; Landry, Samuel J. (The Journal of biological chemistry, 2019)
Effective adaptive immune responses depend on activation of CD4+ T cells via the presentation of antigen peptides in the context of major histocompatibility complex (MHC) class II. The structure of an antigen strongly influences its processing within the endolysosome and potentially controls the identity of peptides that are presented to T cells. A recombinant immunotoxin, comprising exotoxin A domain III (PE-III) from Pseudomonas aeruginosa and a cancer-specific antibody fragment, has been developed to manage cancer, but its effectiveness is limited by the induction of neutralizing antibodies. Here, we observed that this immunogenicity is substantially reduced by substituting six residues within PE-III. Although these substitutions targeted T-cell epitopes, we demonstrate that reduced conformational stability and protease resistance were responsible for the reduced antibody titer. Analysis of mouse T-cell responses coupled with biophysical studies on single-substitution versions of PE-III suggested that modest but comprehensible changes in T-cell priming can dramatically perturb antibody production. The most strongly responsive PE-III epitope was well-predicted by a structure-based algorithm. In summary, single-residue substitutions can drastically alter the processing and immunogenicity of PE-III but have only modest effects on CD4+ T-cell priming in mice. Our findings highlight the importance of structure-based processing constraints for accurate epitope prediction.